The design, development, and evaluation of telepresence interfaces for aging adults: Investigating user perceptions of privacy and usability. Issue 156 (December 2021) - Wu, Xian; Nix, Lauren C.; Brummett, Amanda M.; Aguillon, Cynthia; Oltman, Danielle J.; Beer, Jenay M.
Highlights: Telepresence robots can facilitate age in place and older adults are willing to adapt such technology. Barriers such as usability and privacy issues could precent target population from successfully using telepresence robots. When designing for older adults, their unique physical and cognitive characteristics need to be considered. Older adults expressed positive attitudes towards autonomous features such as obstacle detection. Features that provide users more control over the robot could ease users' privacy concerns. Abstract: Telepresence robots can be beneficial for older adults by helping them stay socially connected and to access telehealth services; both factors are vital in maintaining health and wellness while aging in place. For older adults to willingly use telepresence technology, it is important to ensure that they do not experience barriers to adoption, such as issues with usability and privacy. In this study, we present a two-part research endeavor. Firstly, we developed two telepresence user interfaces (UIs): (1) the control condition—a generic UI design based on currently available telepresence robots; and (2) the experimental condition—a modified UI that was designed specifically for older adults' capabilities and limitations, which also incorporated enhanced privacy features. Secondly, we conducted an in-depth within-subjects mixed-methods assessment of both UIs with 30 older adults (aged M = 71.00, SD = 5.50, range = 61–84 years). Both qualitative and quantitative data yielded positive results, suggesting that older adults perceived the experimental condition to be more usable and private than the control condition. The older adult participants provided insight on which usability and privacy features were perceived as critical, specifying features such as obstacle detection, adjustable robot height, and the ability to restrict room access. By conducting this preliminary study, we investigated what usability features are deemed critical for older adult usage of telepresence. Our goal is to improve the ease of use of telepresence robots, and to enable older adults to remain socially connected while aging in place.